Anti-Blackness/Nativeness and erasure in Mexico: Black feminist geographies and Latin American decolonial dialogues for U.S. urban planning. (2nd January 2021) - Sweet, Elizabeth L.
ABSTRACT: Latin American decolonial scholarship highlights the importance of time, space, and relationship variables in theoretical frameworks, notably different from white-settler philosophical underpinnings that rely on objectivity and modernity. Understanding race and gender in these frameworks has been elusive. I expand urban planning's decolonial project to earnestly engage with race and gender through expanding dialogue with Black feminist geography scholarship. I document the intense and ongoing process of Black/Native erasure and anti-Blackness/Nativeness in Mexico. I claim that if planning practitioners understood the way that white praise and the idea of mestizo travel with Mexican communities in the U.S. along with the afterlife of colonialism, slavery, and genocide, they could link narratives of Black and Native Mexican epistemologies. Planners would be able to more effectively plan with these communities to eliminate exploitative policies and practices and bring planning theory, pedagogy, and practice closer to their decolonial, feminist, and anti-racist aspirations.